2014
DOI: 10.1016/j.bbmt.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Hematopoietic Stem Cells for Transplantation of Hematological Diseases from Related, Haploidentical Donors after Reduced-Intensity Conditioning

Abstract: In a multi-center collaboration, we carried out T-replete, peripheral blood stem cell (PBSC) transplants from related, HLA-haploidentical donors with reduced-intensity conditioning (RIC) and post-transplant cyclophosphamide (Cy) as GvHD prophylaxis in 55 patients with high-risk hematologic disorders. Patients received 2 doses of Cy 50mg/kg IV on days 3 and 4 post-infusion of PBSC (mean 6.4×106/kg CD34+ cells, mean 2.0 ×108/kg CD3+ cells). The median times to neutrophil (500/mcL) and platelet (>20,000/mcL) reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
97
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 21 publications
14
97
5
1
Order By: Relevance
“…This is in accordance with our previous published data 33 and with data from Raj et al 34 The current study has some limitations, mainly due to its retrospective nature. Essentially, diseases and the period of allo-HSCT were significantly different between the 2 cohorts; because the haplo program was initiated after UCB, the follow-up is different and some late events Abbreviations: aGVHD, aGVHD, acute graft-versus-host disease; ANC, absolute neutrophil count; cGVHD, chronic graft-versus-host disease; haplo-HSCT, haploidentical donor allogeneic hematopoietic stem cell transplantation; NRM, nonrecurrence mortality; OS, overall survival; PFS, progression-free survival; PLT, platelet; PT-Cy, posttransplant cyclophosphamide; UCB-HSCT, umbilical cord blood allogeneic hematopoietic stem cell transplantation.…”
Section: Haplo-hsct Ucb-hsctsupporting
confidence: 92%
“…This is in accordance with our previous published data 33 and with data from Raj et al 34 The current study has some limitations, mainly due to its retrospective nature. Essentially, diseases and the period of allo-HSCT were significantly different between the 2 cohorts; because the haplo program was initiated after UCB, the follow-up is different and some late events Abbreviations: aGVHD, aGVHD, acute graft-versus-host disease; ANC, absolute neutrophil count; cGVHD, chronic graft-versus-host disease; haplo-HSCT, haploidentical donor allogeneic hematopoietic stem cell transplantation; NRM, nonrecurrence mortality; OS, overall survival; PFS, progression-free survival; PLT, platelet; PT-Cy, posttransplant cyclophosphamide; UCB-HSCT, umbilical cord blood allogeneic hematopoietic stem cell transplantation.…”
Section: Haplo-hsct Ucb-hsctsupporting
confidence: 92%
“…Full chimerism was defined as 495% donor cells and mixed chimerism as 5% to 95% donor cells. 29 The presence of donor HLAspecific Abs were assessed by solid-phase immunoassays on the Luminex platform, according to the manufacturer's instructions. Sera were tested using polled HLA Ags, HLA class I or class II phenotypes and single HLA Ags panels (One Lambda Inc., Canoga Park, CA, USA).…”
Section: Conditioning Regimen and Gvhd Prophylaxismentioning
confidence: 99%
“…5,6 This strategy has been used in patients with sickle cell anemia 7 and recently in four adults with refractory aplastic anemia. 8 This strategy has not yet been reported in children with aplastic anemia. We report herein our experience of PT/CY haploSCT in two pediatric patients with refractory aplastic anemia.…”
mentioning
confidence: 99%
“…One of the patients failed to engraft but was salvaged by doing a second transplant with a high CD34+ stem cell dose. In a multicentre study reported by Raj et al, 8 55 patients with different hematologic diseases, including 4 patients with refractory aplastic anemia, underwent PBSC haploSCT using PT/CY regimen. Grade II and III acute GVHD was seen in 53% and 8% patients, respectively, but none developed grade IV acute GVHD.…”
mentioning
confidence: 99%